Pengaruh Penggunaan Material Daur Ulang Terhadap Sifat Mekanik Beton Non Pasir - Tommy Iduwin; Dicki Dian Purnama; Pratiwi Septyaning Putri; Hastanto Siswo Martono (Sekolah Tinggi Teknik - PLN, 2020)
Infrastructure development is increasing every year making the need for concrete materials increases. Using alternative materials can reduce the scarcity of material and environmental damage caused by taking and dredging the material. This research is to find out how much influence the recycled material has on the compressive strength of no fines concrete. The variations used are recycled materials of 0%, 25%, 50%, 75% and 100%. Mechanical testing conducted is a compressive strength test to determine the compressive strength of no fines concrete at the age of 7, 14 and 28 days. The ratio of cement and aggregate used is 1: 4 with FAS 0.5. This research uses 15 x 30 cm cylindrical molds with 45 test specimens. The test results show the highest compressive strength value of non-sand concrete occurs at 0% recycled material by 10.47 Mpa and the lowest compressive strength on non-sand concrete 100% recycled material is 8.39 Mpa. The percentage of absorption of no fines concrete shows that the more recycled material is used, the smaller the value of water absorption. The highest absorption value in no fines concrete is 0% recycled material, which is 5.93% and the smallest value is in the variation of no fines concrete 100% recycled material recycled material that is equal to 4.99%.